2019
DOI: 10.1093/jaoac/102.6.1787
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Targeted PCR Method for Raw and Processed Botanical Material Identification: An Example Using Matricaria chamomilla (Chamomile)

Abstract: Background: A requirement of current good manufacturing practices for dietary supplements is that manufacturers must identify their dietary ingredients. DNA-based methods can provide species-level authentication that may sometimes be difficult to achieve using conventional morphological and chemical analysis methods. However, because of varying levels of DNA degradation in botanical materials, many commercial tests fail to generate consistent test results across all types of botanical materials. AOAC published… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Efforts have been made to target DNA fragments according to their degradation level. Studies have shown that species-specific DNA can be amplified from certain processed botanical materials, such as Matricaria chamomilla and Lonicera japonica extracts, and even can be used to differentiate between different varieties of P. ginseng in certain extracts 21 , 29 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Efforts have been made to target DNA fragments according to their degradation level. Studies have shown that species-specific DNA can be amplified from certain processed botanical materials, such as Matricaria chamomilla and Lonicera japonica extracts, and even can be used to differentiate between different varieties of P. ginseng in certain extracts 21 , 29 , 30 , 31 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the application of traditional DNA barcoding should be limited to unprocessed or minimally processed plant materials since DNA degradation in processed materials could result in false-negative results when using universal primers to target barcodes typically longer than 400 bp 22 , 23 . Species-specific PCR, when designed and validated to amplify short DNA fragments (usually less than 200 bp), may have advantages for potentially addressing species identification in heavily processed botanical materials containing partially degraded DNA, such as extracts 21 , 22 . With increased coverage on processed botanical materials, species-specific PCR could be applied to more types of botanical materials in commerce, addressing species identity issues in powders and extracts, which were once difficult to be achieved by other methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…should also not show a false positive due to the specificity of the assay, according to a previous validation study40 .Copyright © 2020 JoVE Creative Commons Attribution-NonCommercial-NoDerivs 3.…”
mentioning
confidence: 84%